Phonological Planning during Sentence Production: Beyond the Verb - Schnur, Tatiana T. (Frontiers in Psychology, 2011)
The current study addresses the extent of phonological planning during spontaneous sentence production. Previous work shows that at articulation, phonological encoding occurs for entire phrases, but encoding beyond the initial phrase may be due to the syntactic relevance of the verb in planning the utterance. I conducted three experiments to investigate whether phonological planning crosses multiple grammatical phrase boundaries (as defined by the number of lexical heads of phrase) within a single phonological phrase. Using the picture-word interference paradigm, I found in two separate experiments a significant phonological facilitation effect to both the verb and noun of sentences like “He opens the gate”. I also altered the frequency of the direct object and found longer utterance initiation times for sentences ending with a low-frequency vs. high-frequency object offering further support that the direct object was phonologically encoded at the time of utterance initiation. That phonological information for post-verbal elements was activated suggests that the grammatical importance of the verb does not restrict the extent of phonological planning. These results suggest that the phonological phrase is unit of planning, where all elements within a phonological phrase are encoded before articulation. Thus, consistent with other action sequencing behavior, there is significant phonological planning ahead in sentence production.